Inward-Looking Policies, Institutions, Autocrats, and Economic Growth in Latin America: An Empirical Exploration - Alberto Chong; Luisa Zanforlin (Inter-American Development Bank, Research Department, 2001)
This paper explores the institutional determinants of economic growth in Latin America by taking advantage of recent empirical research that employs subjective and objective measures to test for a possible Northian explanation that links institutional quality and economic growth. I provide a framework that helps better understand the policymakers` choices and persistence regarding inward-looking policies that were pursued between the 1930s and the 1980s by arguing that in the Latin American case Olson`s (1982) idea of encompassing interest should be expanded to cover not only the economic stakes of power holders, but also, their political stakes, somewhat along the lines of work by Robinson (1997).
Keywords: 330; Wirtschaftswachstum; Institutionelle Infrastruktur; Autoritäres System; Lateinamerika; Governance-Ansatz